A fuzzy comprehensive evaluation algorithm for analyzing electronic word-of-mouth. Issue 6 (3rd June 2017) - Li, Nao; Tung, Vincent; Law, Rob
ABSTRACT: This study evaluates tourism experiences shared through electronic word-of-mouth (eWOM) across four Chinese attractions. The objective is to develop a framework for evaluating eWOM by constructing an indicator system and implementing an analytic hierarchy process with the use of a fuzzy comprehensive evaluation algorithm. This framework is achieved by mapping more than 6000 websites related to Chinese tourism attractions and filtering over 200, 000 useful reviews to measure service performance. Results indicate that ecological–biological attractions failed to make tourists feel "very satisfied" in various aspects, such as overall evaluation, infrastructure, traffic, natural environment, and social environment. Overall, the study contributes by presenting a framework that can be adopted by tourism researchers and industry practitioners to understand tourist preferences and evaluate service performance to improve service quality.